Polynucleotide phosphorylase has an impact on cell biology of Campylobacter jejuni - Haddad, Nabila; Tresse, Odile; Rivoal, Katell; Chevret, Didier; Nonglaton, Quentin; Burns, Christopher M.; Prévost, Hervé; Cappelier, Jean-Michel (Frontiers in Cellular and Infection Microbiology, 2012)
Polynucleotide phosphorylase (PNPase), encoded by the pnp gene, is known to degrade mRNA, mediating post-transcriptional regulation and may affect cellular functions. The role of PNPase is pleiotropic. As orthologs of the two major ribonucleases (RNase E and RNase II) of Escherichia coli are missing in the Campylobacter jejuni genome, in the current study the focus has been on the C. jejuni ortholog of PNPase. The effect of PNPase mutation on C. jejuni phenotypes and proteome was investigated. The inactivation of the pnp gene reduced significantly the ability of C. jejuni to adhere and to invade Ht-29 cells. Moreover, the pnp mutant strain exhibited a decrease in C. jejuni swimming ability and chick colonization. To explain effects of PNPase on C. jejuni 81-176 phenotype, the proteome of the pnp mutant and parental strains were compared. Overall, little variation in protein production was observed. Despite the predicted role of PNPase in mRNA regulation, the pnp mutation did not induce profound proteomic changes suggesting that other ribonucleases in C. jejuni might ensure this biological function in the absence of PNPase. Nevertheless, synthesis of proteins which are involved in virulence (LuxS, PEB3), motility (N-acetylneuraminic acid synthetase), stress-response (KatA, DnaK, Hsp90), and translation system (EF-Tu, EF-G) were modified in the pnp mutant strain suggesting a more specific role of PNPase in C. jejuni. In conclusion, PNPase deficiency induces limited but important consequences on C. jejuni biology that could explain swimming limitation, chick colonization delay, and the decrease of cell adhesion/invasion ability.